MENINGKATKAN HASIL BELAJAR MENGHUBUNGKAN GAYA DENGAN GERAK PADA PERISTIWA DILINGKUNGAN SEKITAR MELALUI METODE DEMONSTRASI PADA SISWA KELAS IV UPT 178 GRESIK - Septi Meliniawati, Diva; Indrawati, Delia; Rismaningtiyas, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In science lessons at UPT 178 Gresik, Wringinanom District, Gresik Regency, the material relating force to motion in events in the surrounding environment tends not to attract students' attention, this is because the teacher uses conventional methods in learning, thus causing student learning outcomes to be below the KKM. The aim of this learning is to improve results learn material relating force to motion in events in the surrounding environment through demonstration methods for class IV students at UPT 178 Gresik, Wringinanom District, Gresik Regency, academic year 2023/2024Learning is carried out in two cycles, cycle I and cycle II, by using questions to measure student learning outcomes, learning outcomes also increase in cycle I 60% to cycle II 95%. The use of the material demonstration method connecting forces with motion in events in the surrounding environment can improve results. studying science for class IV students at UPT 178 Gresik, Wringinanom District, Gresik Regency, academic year 2023/2024.